(E)-2-amino-7-hydroxy-4-styrylquinoline-3-carbonitrile as a novel inhibitor for oil and gas industry: influence of temperature and synergistic agent. Issue 17 (2nd September 2022) - Onyeachu, Ikenna B.; Chauhan, Dheeraj Singh; Quraishi, Mumtaz A.; Obot, Ime B.; Singh, Ambrish
Abstract: For the first time, this work explores the application of a quinolone derivative, namely, (E)-2-amino-7-hydroxy-4-styrylquinoline-3-carbonitrile, in the corrosion inhibition of C1018 steel surface in 3.5% NaCl (CO2 saturated). The quinoline derivative was prepared in a facile single-step method using the microwave-assisted synthesis protocol. A detailed electrochemical analysis using the impedance and polarization measurements was conducted in the present manuscript. The impedance studies revealed increased charge transfer resistance at the metal/solution interface with increasing inhibitor concentrations, suggesting that the inhibitor adsorbed at the metal/electrolyte interface. The polarization measurements exhibited a decline in the corrosion current densities and mixed type of inhibition performance with the cathodic predominance. The inhibitor showed high efficiency of 89% at a dosage as low as 100 ppm. The inhibitor adsorption on the steel surface followed the Langmuir isotherm. The influence of the operational temperature was also investigated at 60 ° C, and the inhibitor revealed a high inhibition efficiency at the higher temperature. The surface analysis revealed the appearance of a smooth surface, which provided support for the adsorption and corrosion inhibition. Computational analysis revealed that the inhibitor adsorbed on the steel surface in the neutral and protonated form, wherein the protonated form showed superior adsorption behavior.